Pemanfaatan Kampung Kota dalam Wisata Warisan Budaya di Kota Singaraja - Komang Wirawan (REKA RUANG, 2021)
Urban settlements have a long, unique history as well as an early marker of the formation of urban civilization. Initially, an urban settlement was a village that was inhabited by traditional society. The modern urban development has made the image of the village faded. Bugis Village is one of several villages that formed Singaraja City at the beginning of the Dutch colonial period which served as a bustling port city. Cultural acculturation as a result of trading activities makes residential areas inhabited by various ethnicities and forms villages with certain ethnic characteristics. The data collection in this study was carried out by means of observation, interviews, and literature study. Furthermore, the collected data were analyzed qualitatively descriptively. The analysis was carried out using theoretical and conceptual guidelines from the results of a literature review on urban villages and cultural heritage tourism. The results of the study stated that the tourism potential of Bugis Village qualifies as cultural heritage tourism based on tangible cultural heritage and intangible cultural heritage that is more than 50 years old and is still well maintained. As a tourist destination, Bugis Village is still in the exploration stage, to realize it, steps are needed such as building revitalization, planning tourist routes, and education and community involvement for the development of urban village tourism.